NEW METHODS OF TEACHING ENGLISH (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
In the modern education system, methods of teaching English are continuously evolving. Traditional approaches are being replaced by interactive and innovative methods that yield effective results in developing students’ language skills. This article explores new teaching methods in English language instruction, including communicative approach, task-based learning, gamification, the use of technology, and differentiated instruction. These new methods enhance students’ confidence, linguistic competence, and cultural awareness. Additionally, the article analyzes the effectiveness of modern teaching strategies and provides recommendations for their practical implementation. This research aims to improve the process of learning English by emphasizing the importance of innovative approaches in education.